2022
DOI: 10.1111/jerd.12883
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual shade matching and photographic shade analysis

Abstract: Objective To compare the performance of a standardized photographic shade analysis (PSA) and visual shade matching (VSM) using two color difference formulas. Materials and Methods Fifty observers (35 undergraduate and 15 graduate students) evaluated the color of two upper left central incisors (LT—light tooth, and DT—dark tooth). VSM was performed using the VITA 3D Master (3D) shade guide in a controlled clinical environment. For PSA, a cross‐polarized filter and a gray card (Whibal) were used to standardize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Although the use of images is not a validated method for color measurements, previous studies have shown that standardizing image acquisition and correcting white balance using a neutral gray card can yield reliable results comparable to those obtained with spectrophotometers. [17][18][19] Another important consideration is the conversion of RGB values to CIELAB color coordinates, which depends on factors like the illuminant and observer angle. 20,24 The choice of an appropriate illuminant was a key parameter in our study, as we aimed to evaluate the color match of single-shade composites to the surrounding substrate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the use of images is not a validated method for color measurements, previous studies have shown that standardizing image acquisition and correcting white balance using a neutral gray card can yield reliable results comparable to those obtained with spectrophotometers. [17][18][19] Another important consideration is the conversion of RGB values to CIELAB color coordinates, which depends on factors like the illuminant and observer angle. 20,24 The choice of an appropriate illuminant was a key parameter in our study, as we aimed to evaluate the color match of single-shade composites to the surrounding substrate.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to ensure accurate color representation in the photographs to obtain reliable results, like those using devices specifically designed for color assessment (e.g., colorimeters). Although the use of images is not a validated method for color measurements, previous studies have shown that standardizing image acquisition and correcting white balance using a neutral gray card can yield reliable results comparable to those obtained with spectrophotometers 17–19 . Another important consideration is the conversion of RGB values to CIELAB color coordinates, which depends on factors like the illuminant and observer angle 20,24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the Vita Toothguide 3D‐Master having been used in several studies, 24,30,41,47–49 no three‐dimensional spatial representation of the 26 physical shade tabs, based on their color coordinates recorded in vivo, had been published prior to this research. Studies with which the present findings may be directly compared are therefore lacking.…”
Section: Discussionmentioning
confidence: 99%